2012
DOI: 10.1111/j.1865-1682.2012.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study to Characterize the Distribution Patterns ofMycobacterium aviumssp.paratuberculosisin Semen, Blood and Faeces of a Naturally Infected Bull by IS 900 Semi-Nested and Quantitative Real-Time PCR

Abstract: Johne's disease is caused by Mycobacterium avium ssp. paratuberculosis (MAP) and has been recognized as an important bacterial infection in ruminants. Although MAP has been detected in semen and within the reproductive organs of bulls, the bacterial distribution and shedding patterns are currently not well characterized. Our investigation was performed to detect and quantify MAP in faeces, semen and blood samples repeatedly drawn from a naturally infected but asymptomatic 18-month-old German Simmental breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
(51 reference statements)
0
21
0
1
Order By: Relevance
“…Others have reported intermittent shedding; however, the interval between positive samples largely depended on the interval between samplings [15, 43]. In the current study, positive fecal samples were followed by negative fecal samples for anywhere from 2 days to 5 weeks before another positive sample was detected.…”
Section: Discussionmentioning
confidence: 66%
“…Others have reported intermittent shedding; however, the interval between positive samples largely depended on the interval between samplings [15, 43]. In the current study, positive fecal samples were followed by negative fecal samples for anywhere from 2 days to 5 weeks before another positive sample was detected.…”
Section: Discussionmentioning
confidence: 66%
“…Nevertheless, the possible distribution of MAP via feces of non‐human primates was not measurable as part of this study, even though it is known from the literature that MAP can be excreted in concentrations of 10 6 MAP genome equivalent/g feces from asymptomatic non‐human primates . Similar MAP concentrations were also measurable in feces of other animals asymptomatically infected, but it is known that the excretion of MAP appears usually intermittently . Hence, it is admitted that diagnostic tests may lead temporarily to negative results during shedding‐free intervals of the animals.…”
Section: Discussionmentioning
confidence: 82%
“…The sensitivity of MAP cultivation from the feces of subclinically infected animals is considered to be 23%‐49%, whereas cultivation of MAP from animals with clinical signs of paratuberculosis is thought to reach a sensitivity of 98% . Also in other studies, a discrepancy between the results of PCR and cultivation was observed . In one of these previous studies, 875 of 1906 (45.91%) investigated fecal samples from dairy cattle were tested positively for the presences of MAP DNA by an IS900‐based real‐time PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common source of infection may be faeco-oral route, contaminated feed, water, milk or colostrums for the calves (Sweeney, 1996). Spreading of the organism through vertical infection to the fetus (Larson and Kopecky, 1970) and infection in semen (Munster et al, 2012) has also been reported. Trangadia et al (2012) found apparent prevalence of JD in Gujarat and Andhra Pradesh 13.39% (true prevalence, 15.68%) and 16.26% (true prevalence, 19.31%) respectively in serological diagnosis.…”
Section: Introductionmentioning
confidence: 99%